Role of Inflammatory and Prognostic Markers and Its Outcome Among Patients with Pre and Post-Operative Colorectal Carcinoma: Markers and Outcomes in Colorectal Carcinoma - Raza, Suhail; Memon, Amir Iqbal; Bhatti, Aisha Masroor; Kumar, Hitesh; Nayab, .; Iqbal, Sayed Hashim (Pakistan Journal of Health Sciences, 2024)
Colorectal carcinoma is a significant health concern, often presenting with symptoms like bleeding per rectum, mucous discharge, tenesmus, altered bowel habits, and weight loss. This study examines the influence of inflammatory and prognostic markers on the outcomes of patients undergoing per and post-operative treatment for colorectal carcinoma. Objective: To evaluate the role of inflammatory and prognostic markers on the outcomes of patients with per and post-operative colorectal carcinoma. Methods: This cross-sectional study included 112 patients aged 20-60 years, of either gender, with symptoms such as bleeding per rectum, mucous discharge, tenesmus, altered bowel habits, and weight loss for ≥1 month, diagnosed with colorectal cancer regardless of stage and grade. Results: The mean age of the patients was 45.16 ± 10.52 years, with 51.8% males and 48.2% females. Common symptoms included abdominal pain, per rectal bleeding, and weight loss, with 89.3% presenting with anemia. Tumors were located in the colon (84.8%) and rectum (28.6%). Pre-operative markers showed elevated WBC in 59.8%, CRP in 87.5%, decreased serum albumin in 77.7%, raised ESR in 61.6%, ferritin in 65.2%, and LDH in 60.7%. Post-operative markers indicated elevated WBC in 92.9%, CRP in 94.6%, decreased serum albumin in 82.1%, raised ESR in 68.8%, ferritin in 69.6%, and LDH in 73.2%. Complications included wound infection, pneumonia, sepsis, and prolonged hospital stays, with a mortality rate of 3.6%. Conclusions: Serum inflammatory markers significantly influence prognoses and predict adverse outcomes in patients undergoing surgical treatment for colorectal carcinoma.